A novel liquid metal patterning technique: voltage induced non-contact electrochemical lithography at room temperature. Issue 1 (28th November 2017) - Yu, Zhenwei; Yun, Frank F.; Wang, Xiaolin
Abstract : Non-contact, maskless, voltage induced electrochemical lithography for liquid metals was demonstrated at room temperature. Abstract : Non-contact, maskless, voltage induced electrochemical lithography for liquid metals was demonstrated at room temperature. Various patterns in liquid metal can be simply and rapidly fabricated using electrochemical hole/dot matrix printing, continuous "writing" and a movable type printing method.